Basic psychological needs and financial well-being among e-commerce outsourcing employees: The role of financial attitude - Anindyastri, Ranty; Risfandy, Tastaftiyan; Arumsari, Septiana Lisa (Jurnal Siasat Bisnis, 2026)
Purpose – This study investigates the relationship between basic psychological needs and financial well-being among outsourced employees in the e-commerce sector of Indonesia, with financial attitude as a mediating variable. Based on Self-Determination Theory (SDT), it aims to explore how the fulfillment of autonomy, competence, and relatedness contributes to positive financial outcomes.Design/methodology/approach – This research applied a quantitative method by collecting survey data from 422 outsourced employees in Indonesia’s e-commerce sector. Data were obtained through an online questionnaire distributed via Google Forms and analyzed using Structural Equation Modeling with the Partial Least Squares (SEM - PLS) technique, using SmartPLS version 4.0.9.9Findings – The research results show that basic psychological needs have a significant positive effect on financial attitude and financial well-being. Financial attitude was found to partially mediate the relationship between psychological needs and financial well-being. When the psychological needs of e-commerce outsourcing employees are fulfilled, they not only feel better emotionally and become more motivated but also exhibit more adaptive financial behaviors. Adaptive financial behavior, combined with positive financial attitudes, can help employees achieve greater financial well-being.Research limitations/implications – This study is limited by its cross-sectional design and narrow employment context, which may affect generalizability. Using self-report surveys alone may not capture the full experiences of outsourced employees. Future research should consider longitudinal methods and qualitative approaches, such as interviews, to explore psychological needs and financial well-being more deeply.Practical implications – Organizations should foster supportive work environments that meet employees’ psychological needs and integrate financial education into employee support programs. This holistic approach can enhance financial well-being, particularly in unstable or outsourced work settings.Originality/value – This study expands the application of Self-Determination Theory within financial behavior by emphasizing how psychological needs influence individuals’ financial attitudes and outcomes. It also highlights the essential role of psychological resources in supporting financial well-being, especially among workers in unstable or uncertain employment conditions.